PENERAPAN KAIDAH-KAIDAH FIQIH DALAM TRANSAKSI EKONOMI DI LEMBAGA KEUANGAN SYARIAH - Iwan Permana (Tahkim (Jurnal Peradaban dan Hukum Islam), 2020)
ABSTRACT The principles of fiqh are born from the Qur'an, al-hadith, and ijma'. The principles of jurisprudence were born with the aim of establishing Islamic law in new issues that continue to develop along with the times, especially in economic transactions or muamalah maliyah which is always developing in Islamic financial institutions. Thus the principles of fiqh are the products of ijtihad and are generalizations of fiqh themes that are spread among the school of ulemas. The existence of the rules of fiqh is a necessity to obtain the ease of knowing contemporary laws, especially economic issues, many of which do not have a sharîh text (a definite proposition) in the Qur'an or hadith. Similarly, to make it easier to master the problems of furu'iyyah (branches) that continue to grow and countless, especially in economic problems that develop in Islamic financial institutions. Keywords: Transactions, Economy, Rules, fiqh